Paths of Speech: Symbols, Sociality and Subjectivity among the Muinane of the Colombian Amazon - Londoño Sulkin, Carlos David (Ethnologies, 2003)
AbstractThe Muinane, an indigenous group of the Colombian Amazon, narratively present individual subjectivity as stemming from cultivated substances that constitute the bodies of human beings, or else from wild substances that usurp the role of proper stuffs. Moral subjectivity in particular stems from the tobacco, coca and other substances shared by a community. Subjectivity in such an account is both individual and collective, and either divine or animalistic as well. Muinane people’s rhetoric at times seems to present subjectivity as radically determined by extra-individual entities. However, the author argues that consciousness of the self is very much a part of their accounts of action — that is, that they understand their own actions to be self-directed as well as other-directed, and furthermore, that their ways of speaking about their own social interactions and thoughts/emotions performatively shape them. The author stresses the achieved character of social life and the intrinsically social character of selfhood, without making a case for a monolithic culture that monologically determines subjectivity and sociality.